Hematologic profile in a Persian cat with osteosarcoma - Prasaja, Aditya Gilang; Mutiara, Chika Khaerani; Wijaya, Stevanie Andrea; Lestari, Nurul Aeni Ayu; Santoso, Fransiskus Teguh; Windria, Sarasati (ARSHI Veterinary Letters, 2025)
A three-year-old Persian cat presented to the West Java Provincial Veterinary Hospital with swelling in the left front leg and was diagnosed with osteosarcoma. This study aimed to evaluate the impact of osteosarcoma on the haematological profiles of cats. Humerus amputation is the standard treatment. A detailed haematological assessment was performed, including red blood cell count, white blood cells count, lymphocytes, monocytes, immature cells, mid-sized cells, granulocytes, haemoglobin, haematocrit, MCV, MCH, MCHC, and platelets. The findings revealed leukocytosis, granulocytosis, hypochromic macrocytic anaemia, and thrombocytopenia, indicating that osteosarcoma may disrupt the normal blood component production.